HUBUNGAN PENGETAHUAN PERAWAT PELAKSANA TERHADAP PEMBERIAN TERAPI NUTRISI PER NGT DI RSUP. PROF. DR. R. D. KANDOU MANADO - Dylan Tamalsir; Masumbauw Jenifer J A; Siahaan Junita; Rosdiana Mus; Presli G Siahaya (Fakultas Kedokteran Universitas Pattimura, 2023)
Nutrients are substances that can affect health and disease. Someone who consumes less nutrition has a greater risk of experiencing malnutrition compared to consuming enough nutrition. The process of providing nutrition itself is very complex so that it requires good knowledge and collaboration between health professionals, including nurses who have responsibilities and roles in the management of nutritional therapy. This study aims to determine the relationship between the knowledge of the implementing nurse and the provision of nutritional therapy per NGT at RSUP Prof. Dr. R. D. Kandou Manado. The research design used was analytic observational with a cross sectional approach. The sample selection technique used was purposive sampling with a sample of 90 nurses. The results of this study showed that there was no significant relationship between the knowledge of the implementing nurse and the provision of nutritional therapy per NGT with an α 0.208 > 0.05.